Remote Interpreting in the Context of University Training in Slovakia During the Covid-19 Pandemic - Birčák, Andrej (Research in Language, 2025)
Remote interpreting experienced rapid expansion during the COVID-19 pandemic. Although there are no pandemic restrictions today in Slovakia, the interpreting market has not returned to its pre-pandemic state. Presented chapter examines how Slovak universities prepared future interpreters during online education, especially in regard to remote interpreting. Focus group and individual interviews were conducted with 15 interpreting teachers from all Slovak universities that are offering translation and interpreting program. Analysis revealed a lack of systematic integration of remote interpreting in the university training before and during the pandemic; problems with finding a suitable videoconferencing platform for the training; both good and bad practices. Exploring remote interpreting during the pandemic era helps understand the current practices in the training and the market.